The Impact of Spin-Off Policy To The Profitability On Indonesian Islamic Banking Industry - Hamid, Abdul (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2015)
The purpose of this paper is to analyze that the spinoff policy that based on Islamic Banking Act No. 21/2008 had an impact on the profitability ratio of Islamic banking industry in Indonesia. This research used ordinary least square regression. The variable used in this paper is spin-off which is used as a dummy variable, and also included the internal factor of industry such as deposit margin, non-performing financing (NPF), and efficiency ratio (measured by BOPO). The result showed that dummy variable of spin-off, NPF and BOPO had an impact on the profitability in Indonesian Islamic banking industry. The implication of this result is spin-off policy had a good impact on the profitability in Indonesian Islamic banking industry. According to this result, Bank Indonesia should stimulate the Islamic banking unit to spin-off from their parents conventional banks.DOI:10.15408/aiq.v7i1.1363